2022
DOI: 10.52436/1.jpti.183
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Media Animasi Berbasis Aplikasi Renderforest Dalam Membentuk Kepribadian Islami Bagi Siswa Sekolah Dasar Kelas 4

Abstract: Perkembangan zaman di era teknologi saat ini membuat sebagian besar anak – anak yang duduk di Sekolah Dasar lebih tertarik menonton cerita edukasi di smartphone ketimbang membaca sebuah cerita dibuku. Maka dari itu menjadi sebuah tantangan bagi tenaga pendidik dalam membuat video pembelajaran berbasis teknologi. Kurangnya pemahaman tenaga pendidik pada teknologi membuat media pembelajaran kurang menarik sehingga motivasi anak akan menurun. Penelitian ini membantu para pendidik dalam membuat media pembelajaran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…This media must be able to increase learning motivation, can be used and direct students' attention to the media, and have the ability to provide responses, feedback including encouraging students to carry out learning practices correctly so that they can be developed using Render Forest media. The Render Forest application is software that is used for certain purposes, such as processing documents, managing windows and games and so on (Destiani et al, 2023;Nur Aeni et al, 2022). The Render Forest application is software that offers free video production services online (Alamsyah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This media must be able to increase learning motivation, can be used and direct students' attention to the media, and have the ability to provide responses, feedback including encouraging students to carry out learning practices correctly so that they can be developed using Render Forest media. The Render Forest application is software that is used for certain purposes, such as processing documents, managing windows and games and so on (Destiani et al, 2023;Nur Aeni et al, 2022). The Render Forest application is software that offers free video production services online (Alamsyah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The Render Forest application is software that offers free video production services online (Alamsyah et al, 2023). Free tools enable you to create professional quality presentations, intros, slideshows and more (Nur Aeni et al, 2022;Sari & Fathoni, 2022). Render Forest offers the best solution for that.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers carry out the design stage by creating material designs that can support the learning process in the Ispring ,application, including materials, images, audio, qu,estions, and answer keys, media designed by researchers is easier and more enjoyable (Nur Aeni, Nur Nofriani, Ayuni Fauziah, & Ahmad Fauzi, 2022). In this media, researchers prepare quizzes for students programmed to produce scores and discuss true and false questions.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have revealed that using Android applications can increase students' willingness and learning concepts for better learning outcomes (Aeni et al, 2022). The results of other studies reveal that learning using the Renderforest application is the most effective method for increasing student learning motivation (Wulandari & Putra, 2021).…”
Section: Introductionmentioning
confidence: 99%